Determination of physical and mechanical properties of plywood produced using beech, okoume and ozigo species - BİRİNCİ, Emre (Cankiri Karatekin Universitesi, 2022)
Wood and wood-based materials are widely used in the construction industry in the world. The sustainable and renewable nature of wood is seen as an important advantage in contrast to non-renewable resources such as aluminum, steel, concrete, and plastic. In order to protect the advantages of wood and eliminate / reduce its disadvantages, plywood, particle board, fiber board, LVL, CLT, wood plastic composites etc. such as new wood-based engineering products are produced. Plywoods are widely used in automotive, construction, furniture, and many industries. In our country, plywoods are produced using tropical species as well as native tree species. In this study, density, water absorption, thickness swelling, bending resistance, elasticity of modulus in bending and shear strength values of plywood made of beech, okoume and ozigo wood species are investigated. Comparison of plywood produced from tropical species with beech has been made. It has been determined that beech plywood has higher density than okoume and ozigo plywood. It has been determined that beech plywood has higher density than okoume and ozigo plywood. It has been observed that there is a linear relationship between the bending strength, elasticity modulus and shear strength values of beech plywood and their full dry density.
Keywords: 15. Life on land; 7. Clean energy; 12. Responsible consumption